Biochemical and molecular basis of pesticide degradation by microorganisms - Singh, B.K; Kuhad, R.C; Singh, A; Lal, R; Tripathi, K.K (Critical reviews in biotechnology, 1999)
Use of synthetic pesticides has become an indispensable tool in agriculture for the control of pests. It is estimated that about 4 million tons of pesticides are applied to world crops annually for pest control. Less than 1% of the total applied pesticides generally gets to the target pests. Therefore, most of the pesticide remains unused and enters into the ecosystem. This excessive pesticide residue accumulates in the biosphere and creates ecological stress. Soil and water are the ultimate sink for excessive pesticides. The use of chemical pesticides cannot be discontinued despite their persistence in the environment, their tendency toward bioaccumulation and toxicity to nontarget organisms, including human beings as well as the toxicological and environmental problems of its residues. Therefore, search of remedies and techniques for decontamination and detoxification of pesticide-contaminated environments has become an important subject of research. Bioremediation seems to be one of the most environmentally safe and cost-effective methods for this purpose. Microorganisms seem to be the most efficient bioremedial agents, and many soil microbes are known to degrade pesticides. The available literature on microbial degradation of xenobiotics indicates that many studies have mainly considered two aspects: (1) the fundamental basis of biodegradation activities, and the evolution and transfer of such activities among microbes, and (2) bioremediation techniques to detoxify severely pesticide-contaminated environments. However, the use of the microorganisms for bioremediation requires an understanding of all the physiological, microbiological, and biochemical aspects involved in pollutant transformation.